Von Willebrand disease: diagnosis and management. Issue 8 (August 2019) - Williams, Michael; Lancashire, Jonathan
Abstract: Von Willebrand Disease is a common cause of excessive bruising and bleeding in children. This short article gives advice on diagnosis and management for paediatricians. Given its prevalence and presenting symptoms, VWD should always be considered in the assessment of children suspected of non-accidental injury. Its diagnosis can be challenging, not only because of the various subtypes of the disorder but because of the considerable overlap between VWD and normal individuals. Laboratory diagnosis requires a range of quantitative and qualitative tests of the VWF protein, with targeted gene analysis increasingly used to confirm the diagnosis of type 2 and type 3 VWD. Bleeding Assessment Tools may be helpful in directed laboratory testing but are often less so in young children who have had limited haemostatic challenges. Treatment for VWD includes the use of antifibrinolytic drugs, vasopressin or VWF-containing clotting factor concentrates. Treatment is often on-demand for individual bleeding episodes but there are specific indications for the use of prophylactic treatment in children.